2008
DOI: 10.1257/aer.98.3.1009
|View full text |Cite
|
Sign up to set email alerts
|

Historical Property Rights, Sociality, and the Emergence of Impersonal Exchange in Long-Distance Trade

Abstract: Specialization and exchange are at the core of economics, yet over 230 years after Adam Smith first presented his fundamental theorem, economists know remarkably little about how exchange evolves from personal social interactions-reinforced by local knowledge, reputations, and the prospect of future dealings-to impersonal market transactions undergirded by such formal institutions as impartial courts. Smith, however, merely posited the phenomena of specialization and exchange as an expression of a "propensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(41 citation statements)
references
References 4 publications
1
40
0
Order By: Relevance
“…A rapidly growing literature supports these observations. For example, Kimbrough et al (2006) found that it is more common to mention “we” or “us” during chat with in-group rather than out-group members, and that the mention of these encompassing words is positively correlated with cooperation and the willingness to make and keep promises to do personal favors. Schniter et al (2012) concluded from their experiments that one of the steps for effectively restoring damaged trust with a partner is to convey “a shared welfare or other-regarding perspective.”…”
Section: The Game Messages and Evaluationsmentioning
confidence: 99%
“…A rapidly growing literature supports these observations. For example, Kimbrough et al (2006) found that it is more common to mention “we” or “us” during chat with in-group rather than out-group members, and that the mention of these encompassing words is positively correlated with cooperation and the willingness to make and keep promises to do personal favors. Schniter et al (2012) concluded from their experiments that one of the steps for effectively restoring damaged trust with a partner is to convey “a shared welfare or other-regarding perspective.”…”
Section: The Game Messages and Evaluationsmentioning
confidence: 99%
“…Bisin and Verdier (2001), Tabellini (2008b), and Guiso et al (2008) focus primarily on the intra-family transmission process, while Dohman et al (2012) highlight the role of assortative mating and the local environment. Bisin and Verdier (2017), Kimbrough et al (2008), Greif and Tadelis (2010), and Iyigun and Rubin (2017) provide arguments for how culture and institutions interact. 4 While one can run a test for pre-existing differences on either side of the discontinuity (e.g., Becker et al 2016), such data from the pre-existing period are often much worse due to their historical nature and are subject to omitted variable bias.…”
Section: Introductionmentioning
confidence: 99%
“…To shed more light on these strategies we infer the contents of representative chat protocols. In this regard we follow Kimbrough et al (2008) and Fonseca and Normann (2012) who have shown that quoting chat protocols of experiments may be very helpful for further revealing promising information about subjects' strategies.…”
Section: Analysis Of the Chat Protocolsmentioning
confidence: 94%
“…8 The communication option also allows us to to understand the underlying motivations of colluding rms, i.e., whether rms may care about payo asymmetries between inside/outside rms in partial cartels. We therefore evaluate communication following the approaches used in Andersson and Wengström (2007) and Kimbrough et al (2008) in order to infer whether or not payo asymmetries inuence the formation of partial cartels.…”
mentioning
confidence: 99%